2003
DOI: 10.1007/s005950300023
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Carcinoma of the Breast with a Cystically Dilated Intraductal Component: Report of a Case

Abstract: A case of secretory carcinoma of the breast in a 61-year-old woman is described. She came to our hospital complaining of a bloody nipple discharge. The physical examination revealed a 2.8 x 2.1-cm, firm, irregular lump with bloody nipple discharge in her left breast. Mammography demonstrated an irregular mass and ultrasonography showed an irregular hypoechoic mass accompanied with a cyst. Ductgraphy was done. It showed a dilated mammary duct leading to the cyst which was partially occupied with carcinoma. A cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The intraductal carcinoma may extend beyond the confines of the grossly evident tumor. Multifocal gross lesions, and cystically dilated intraductal components have been described [13,14]. Most commonly, the intraductal carcinoma is papillary or cribriform.…”
Section: Discussionmentioning
confidence: 99%
“…The intraductal carcinoma may extend beyond the confines of the grossly evident tumor. Multifocal gross lesions, and cystically dilated intraductal components have been described [13,14]. Most commonly, the intraductal carcinoma is papillary or cribriform.…”
Section: Discussionmentioning
confidence: 99%
“…6,10,11 The presenting symptom is usually a mobile and palpable mass, but in a few cases patients have a bloody nipple discharge. 2,3,8 In this study, 3 patients had a palpable and nontender mass, and 1 had a nipple discharge. This tumor is frequently located in the subareolar region but may occur in any part of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…Secretory carcinoma of the breast is so named because the characteristic histologic features of the tumor are abundant periodic acid-Schiff-positive secretions in both cells and tubular acini and tumor cells that are typically vacuolated with abundant secretory materials ( Figure 1). [1][2][3][4] This tumor tends to have rare locoregional recurrence and is associated with prolonged survival. 1,[3][4][5] In a literature review from a report by Ozguroglu et al, 6 distant metastasis was found in only 6 of 121 cases.…”
mentioning
confidence: 99%
“…This long natural course of the disease points out the importance of surgery in young patients despite locally advanced disease. None of the metastatic cases responded to chemotherapy and actually, none of the patients during childhood had adequate, standard surgery (table 1) [15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52]. …”
Section: Discussionmentioning
confidence: 99%